Improving Children's Learning Outcomes in Recognizing Letters of the Alphabet Using Active Student Learning for Group B Students - Maulidah Maulidah; Muhammad Zulkarnaen; Noor Baiti; Muhammad Yusuf (EDUJAVARE: International Journal of Educational Research, 2025)
Early childhood literacy development is a fundamental aspect of education because the ability to recognize alphabet letters forms the basis for reading and writing skills. However, many kindergarten children still experience difficulties in identifying and pronouncing letters due to limited engagement and monotonous teaching methods. This study aimed to improve children’s learning outcomes in recognizing alphabet letters through the implementation of Student Active Learning (SAL) in Group B students at ABA Sei Besar Kindergarten. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model conducted in two cycles involving 12 children aged 5–6 years. Data were collected through observation, learning outcome assessments, field notes, and documentation, then analyzed descriptively using percentage techniques. The findings revealed a significant improvement in children’s alphabet recognition skills after the application of SAL. Learning mastery increased from 42% in the pre-action stage to 79.1% in Cycle I and reached 95.1% in Cycle II. Children became more active, motivated, confident, and collaborative during learning activities involving games, group discussions, and hands-on letter recognition tasks. The study concludes that SAL is an effective and engaging approach for improving early childhood literacy outcomes, particularly alphabet recognition. This research contributes to the development of active learning strategies in early childhood education by emphasizing participatory and child-centered literacy instruction.